The answer is 3/4 and it was already simplified
Answer:
8 and 9
Step-by-step explanation:
Answer:
-37
Step-by-step explanation:
It would be greatly appreciated if you gave me brainlest
Answer:
see explanation
Step-by-step explanation:
(a)
A recursive formula allows any term in the sequence to be found by adding the common difference d to the previous term.
Here d = - 4 , then recursive formula is
=
- 4 with a₁ = 2
(b)
The explicit formula for an arithmetic sequence is
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Here a₁ = 2 and d = - 4, thus
= 2 - 4(n - 1) = 2 - 4n + 4 = 6 - 4n ← explicit formula
(c)
Using the recursive formula
a₁ = 2
a₂ = 2 - 4 = - 2
a₃ = - 2 - 4 = - 6
Using the explicit formula
a₅ = 6 - 4(5) = 6 - 20 = - 14
a₁₀ = 6 - 4(10) = 6 - 40 = - 34
a₁₀₀ = 6 - 4(100) = 6 - 400 = - 394
Answer:
An undefined term is a term that can't be defined so easily. There really isn't a definition to define such terms. Consider the word "the." We use the word "the" all of the time, but do we really know how to define the word "the?" "Am" is another word that can't be defined so easily.